Metodologías y Normas en Plataforma Tecnológica para la Gestión de Comunidades Académicas y Recreativas de la Universidad Técnica de Babahoyo. - Moran Vera, Yefer Eduardo (2024)
The main objective of this curricular integration work is to evaluate the standards and methodologies applied in the “Technological Platform for the Management of Academic and Recreational Communities of the Technical University of Babahoyo”, which is a mobile application developed thanks to a seed project within the institution in the period 2023-2024. Methodologies and standards are crucial in the development and management of projects, as they help these to meet the requirements and deadlines established, allowing to improve the work environment and the results of the team. In a conceptual framework, methodologies are processes that standardize actions for efficiency and effectiveness, within a framework and context, in this paper we mention development methodologies and standards, such as Scrum, Kanban, XP, which include a diversity of techniques and tools to help and enrich projects based on agile methodologies.